“Defenders of Perversion”: Professing Same-Sex Marriage Rights in the Local Press - Osborne, Geraint B.; Wilton, Shauna (Engaged Scholar Journal, 2022)
This case study provides an important socio-historical snapshot of the same-sex marriage debate in a small city in central Alberta between December 2004 and August 2005. We explore the relationship between professors and small-town newspapers in fostering democratic dialogues on key social issues through an analysis of faculty columns and the responding Letters to the Editor in a local paper. In so doing, this research focuses on two social groups located in a particular social environment, each representing a particular frame: the professors working in the local university who maintained an op-ed column in the local paper and supported a equality frame; and the general public living in Camrose and the surrounding rural area who supported a morality frame. This article contributes to our understanding of scholarly engagement in the town-gown context, the democratic role of the press, and how a particularly contentious social and political issue—same-sex marriage—was experienced and framed by concerned citizens in a small conservative rural city that is also the home to a liberal arts and sciences university campus.